Chapter 1 Heritages, identities and Europe Exploring cultural forms and expressions - Kockel, Ullrich (Taylor & Francis, 2019)
Traditional arts practices and festivals have attracted increasing and diverse attention in the European context since policymakers discovered 'culture' as a resource in the 1980s (see, e.g., Kilday 1998 ). Their impact on their respective communities of practice, modes of production and exchange value in contemporary European society is under the spotlight from various angles within the newly emerged fi eld of 'festival studies', which is deeply connected to policy issues (Frost 2016 ). However, much of this interest is instrumentally concerned with revenue potential, leaving key concepts, such as heritage, identity and indeed Europe, defi ned in rather vague and often contradictory terms (Kockel, Nic Craith and Frykman 2012 ; Logan, Kockel and Nic Craith 2015 ; K ø lvraa 2016 ; L ä hdesm ä ki 2016 ; Whitehead and Bozo ğ lu 2017 ). Moreover, the number and range of events labelled as 'festival' is growing (Frost 2016 : 569), requiring a broader perspective on performances of heritage and identity.